DAMPAK POLITIK TRANSAKSIONAL DALAM PEMILU TERHADAP TINDAK PIDANA KORUPSI - Subihat, Ihat (Bawaslu Provinsi Jawa Barat, 2021)
The prevention and eradication of criminal acts of corruption cannot rely solely on law enforcement; all stakeholders must collaborate. Bureaucratic arrangement, governance arrangement, political arrangement, economic arrangement, and cultural arrangement are all critical to preventing transactional politics from occurring in the legislative, executive, and judicial branches. There are many facts in the trial of corruption cases that should be suspected as a result of transactional politics carried out by state officials during their candidacy. Good governance is in line with democratic principles that are fair, honest, wise, independent, with integrity, responsibility, discipline, humility, and professionalism, as well as tested and measurable. Transactional politics becomes the embryo of corrupt behavior. As a result, four fundamental issues can be addressed to prevent corrupt behavior: neutral law; fair law enforcement ofcials; responsive community legal culture; and bureaucratic empowerment.